Systemic use of models in the teaching of natural and mathematical disciplines as one of the effective fundamentalization methods of future teachers training (Pedagogy of Higher and Secondary Education, 2015)
Rykova L. L. Systemic use of models in the teaching of natural and mathematical disciplines as one of the effective fundamentalization methods of future teachers training.Based on the analysis of the nature and functions of education fundamentalization three didactic conditions of use of models in teaching natural and mathematical disciplines for thepurpose of realization of the basic principles of a fundamentalization of future teachers training have been offered.
Keywords: education fundamentalization; the use of models; future teachers training